2018
DOI: 10.2340/16501977-2280
|View full text |Cite
|
Sign up to set email alerts
|

Berg Balance Scale score at admission can predict walking suitable for community ambulation at discharge from inpatient stroke rehabilitation

Abstract: The Berg Balance Scale can be used at rehabilitation admission to predict the degree of improvement in walking for patients with stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
73
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 33 publications
10
73
1
5
Order By: Relevance
“… The Barthel Index (BI) was used to measure performance in activities of daily living (ADL) [ 27 ]. The Berg Balance Scale (BBS) was used to determine patient’s ability (or inability) to safely balance during a series of predetermined tasks [ 28 ]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… The Barthel Index (BI) was used to measure performance in activities of daily living (ADL) [ 27 ]. The Berg Balance Scale (BBS) was used to determine patient’s ability (or inability) to safely balance during a series of predetermined tasks [ 28 ]. …”
Section: Methodsmentioning
confidence: 99%
“…The Berg Balance Scale (BBS) was used to determine patient's ability (or inability) to safely balance during a series of predetermined tasks [28].…”
mentioning
confidence: 99%
“…Various clinical tools have been developed to identify individuals at high risk of falling (6). Of these, the Berg Balance Scale (BBS), the Timed Up and Go (TUG) and the Functional Reach Test (FRT) are widely used for their convenience and availability of cut-off values to identify those at risk of falling (7)(8)(9)(10). The cut-off values (to differentiate fallers from non-fallers) for these tests, however, vary depending on individuals' characteristics and the length of follow-up (11,12).…”
mentioning
confidence: 99%
“…In addition, BBS and walk test performance in BG became better than that in the CG. BBS can reflect the degree of walking improvement for patients with stroke, [ 48 ] and predict the risk of falls. [ 49 ] All in all, it is suggested that BW can be used as an effective method to improve some gait indices, balance and walking ability of stroke patients.…”
Section: Discussionmentioning
confidence: 99%